The Utility of Upcoming Fish Models in Homoeopathy: A Scoping Review (Advancements in Homeopathic Research, 2024)
Background: Fish is the earliest, most prolific, and  most diversified class of vertebrates with around  34,000 species. Various species of fish have been used  as research models all around the world to provide  insights into intricate human genetics, anatomical  and physiological systems, and the pathophysiology  of human illnesses.  Aim: This study aimed to highlight experimental  studies of fish models in Homoeopathy using a variety  of evaluation parameters along with validated  analytical tools for traceable evidence.  Methods: The information was gathered for  preclinical research studying the impact of  Homoeopathic formulations on disorders in a variety  of fish, from a number of databases such as Scopus,  Science Direct, Web of Science, PubMed, Research  Gate, and Google Scholar.  Result: There were 30 publications in all that were  evaluated, and of them, 25 met the inclusion criteria  and were included in the scoping review. Conclusion:  The use of fish models in Homoeopathic research can  be considered to be valuable as it gives a versatile  approach that can significantly contribute to our  understanding of biology, disease, and environmental  science. Subsequently, the fish models enhance the  ability of researchers to make advanced discoveries  in various fields of study.
Keywords: Fish; model organisms; Homoeopathy; in vivo study; scoping review